Highly Potent Metallopeptide Analogues of Luteinizing Hormone-Releasing Hormone - Bajusz, S.; Janaky, T.; Csernus, V. J.; Bokser, L.; Fekete, M.; Srkalovic, G.; Redding, T. W.; Schally, A. V. (Proceedings of the National Academy of Sciences - PNAS, 1989)
Metal complexes related to the cytotoxic complexes cisplatin [cis-diamminedichloroplatinum(II)] and trans-bis(salicylaldoximato)copper(II) were incorporated into suitably modified luteinizing hormone-releasing hormone (LH-RH) analogues containing D-lysine at position 6. Some of the metallopeptides thus obtained proved to be highly active LH-RH agonists or antagonists. For instance, SB-40, a PtCl2-containing metallopeptide in which platinum is coordinated to an N-ε(DL-2,3-diaminopropionyl)-D-lysine residue [D-Lys(DL-A2pr] at position 6, showed 50 times higher LH-releasing potency than the native hormone. SB-95, [Ac-D-Nal(2)1, D-Phe(pCl)2,D-Pal(3)2, Arg5, D-Lys{Dl-A2pr(Sal2Cu)}$^{6}$ , D-Ala10]LH-RH, where Nal(2) is 3-(2-naphthyl)alanine, Pal(3) is 3-(3-pyridyl)alanine, and copper(II) is coordinated to the salicylideneimino moieties resulting from condensation of salicylaldehyde with D-Lys(Dl-A2pr)6, caused 100% inhibition of ovulation at a dose of 3 μ g in rats. Most metallopeptide analogues of LH-RH showed high affinities for the membrane receptors of rat pituitary and human breast cancer cells. Some of these metallopeptides had cytotoxic activity against human breast cancer and prostate cancer cell lines in vitro (this will be the subject of a separate paper on cytotoxicity evaluation). Such cytostatic metallopeptides could be envisioned as targeted chemotherapeutic agents in cancers that contain receptors for LH-RH-like peptides.